Peran Efektivitas Literasi Keuangan dan Pembiayaan Syariah Terhadap Stabilitas Keuangan UMKM - Sriyono; Dhea Ariesta Putri; Muhammad Rizki Alwi Ardana; Nila Osama; Moch Zaky Zamani (Journal of Trends Economics and Accounting Research, 2023)
MSMEs have great potential in driving macroeconomic development in Indonesia, but are faced with various internal and external challenges. This article aims to analyze the factors that affect the financial stability of MSMEs, with a focus on financial literacy and Islamic financing. The research method used is Literature Review Study (SLR), by collecting secondary data from various articles. The data analysis technique involves synthesizing and interpreting information from relevant literature. The results showed that financial literacy has a positive and significant influence on the financial performance of MSMEs. SNLIK results In 2022, the financial literacy of Indonesians reached an improved level to 49.68%, while financial inclusion increased to 85.10%. This comparison shows an increase from the 2019 National Survey on Financial Literacy and Inclusion (SNLIK) results, where financial literacy was 38.03% and financial inclusion was 76.19%. Financial literacy, which includes an understanding of financial management, financial services institutions, financial products and services, plays a crucial role in helping MSMEs make informed financial decisions. Data from the National Financial Literacy Index shows a positive increase, but further efforts are still needed to improve the financial literacy of MSMEs. In addition to financial literacy, Islamic financing from Islamic banks also contributes to improving the financial performance of MSMEs. The growth of Islamic financing over the past few years shows that Islamic banks have an important role in supporting MSMEs. However, there are still challenges such as the lack of public knowledge about Islamic banking and the lack of human resources (HR) to reach more networks. In conclusion, improving financial literacy and utilization of Islamic financing can be an effective strategy to improve the financial stability of MSMEs in Indonesia. Efforts to improve financial literacy and public understanding of Islamic finance are expected to be the focus of policies that support the growth and stability of MSMEs.